A Study Of 100 Cases of Brachial Plexus - Ojaswini Malukar; Ajay Rathva (Medsci Publications, 2011)
Brachial Plexus innervates the upper limb. As it is the point of formation of many nerves, variations are common. The presence of anatomical variations of the peripheral nervous system is often used to explain unexpected clinical signs and symptoms. Therefore, it is of importance to anatomists, radiologists, anesthesiologists and surgeons. The current research work was aimed to study common and anomalous variations of brachial plexsus and communication between its branches. The present study was done on 50 cadavers to study 100 brachial plexuses, 50 each of right and left upper limbs. 10 cases showed absence of musculocutaneous nerve and 8 cases of communication between musculocutaneous and median nerve. 18% of cases showed significant variations which can have bearing on surgical procedures.